The Epidemiological Impact of an HIV Vaccine on the HIV/AIDS Epidemic in Southern India - Nagelkerke, Nico J.D.; De Vlas, Sake J. (World Bank, Washington, DC, 2014)
The potential epidemiological impact of preventive HIV vaccines on the HIV epidemic in Southern India is examined using a mathematical deterministic dynamic compartmental model. Various assumptions about the degree of protection offered by such a vaccine, the extent of immunological response of those vaccinated, and the duration of protection afforded are explored. Alternative targeting strategies for HIV vaccination are simulated and compared with the impact of conventional prevention interventions in high-risk groups and the general population. The impact of disinhibition (increased risk behavior due to the presence of a vaccine) is also considered. Vaccines that convey a high degree of protection in a share of or all of those immunized and that convey life-long immunity are the most effective in curbing the HIV epidemic. Vaccines that convey less than complete protection may also have substantial public health impact, but disinhibition can easily undo their effects and they should be used combined with conventional prevention efforts. Conventional interventions that target commercial sex workers and their clients to increase condom use can also be highly effective and can be implemented immediately, before the arrival of vaccines.